2016
DOI: 10.1007/s11920-015-0642-5
|View full text |Cite
|
Sign up to set email alerts
|

Withdrawing Benzodiazepines in Patients With Anxiety Disorders

Abstract: The large class of CNS-depressant medications-the benzodiazepines-have been extensively used for over 50 years, anxiety disorders being one of the main indications. A substantial proportion (perhaps up to 20-30 %) of long-term users becomes physically dependent on them. Problems with their use became manifest, and dependence, withdrawal difficulties and abuse were documented by the 1980s. Many such users experience physical and psychological withdrawal symptoms on attempted cessation and may develop clinically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 70 publications
0
38
0
7
Order By: Relevance
“…Benzodiazepine discontinuation is known to produce minor as well as major new withdrawal symptoms. Table 4 reports most frequent minor new withdrawal symptoms [37][38][39][40][41], among them sweating, tachycardia, nausea, visual changes, tremor, confusion, restlessness. Major withdrawal symptoms, such as seizure [42,43] and psychosis [43], are rare.…”
Section: New Withdrawal Symptoms After Benzodiazepine Discontinuationmentioning
confidence: 99%
See 1 more Smart Citation
“…Benzodiazepine discontinuation is known to produce minor as well as major new withdrawal symptoms. Table 4 reports most frequent minor new withdrawal symptoms [37][38][39][40][41], among them sweating, tachycardia, nausea, visual changes, tremor, confusion, restlessness. Major withdrawal symptoms, such as seizure [42,43] and psychosis [43], are rare.…”
Section: New Withdrawal Symptoms After Benzodiazepine Discontinuationmentioning
confidence: 99%
“…Management of Benzodiazepine Discontinuation Slow tapering, often extending over a year or more, has been suggested to manage new withdrawal symptoms [78]. However, even a more flexible tapering at a rate that the patient can tolerate, typically in about 3-6 months, has shown to be appropriate [37]. Some authors suggested tapering from other BZDs such as lorazepam after substituting diazepam [79], according to Murphy and Tyrer [80] such substitution has shown little evidence to support its efficacy.…”
Section: Associated Clinical Manifestationsmentioning
confidence: 99%
“…The prevalence of mood and anxiety disorders including posttraumatic stress disorder (PTSD), panic disorder, and generalized anxiety disorders underscores the critical need for innovative treatment approaches for this class of disorders. The current primary treatment for these disorders produces a delayed onset of action with modest therapeutic benefits and significant adverse effects (3), while the chronic use of the fast-acting benzodiazepines treatment can cause potentially significant adverse effects (46). …”
Section: Introductionmentioning
confidence: 99%
“…There is synergism between these two respiratory depressants (National Institute on Drug Abuse, 2018), which has been implicated in the drug-related mortality increase seen by emergency departments in the United States (Gomes, Mamdani, Dhalla, Paterson, & Juurlink, 2011). As with opioids, BZDs are addictive (Lader & Kyriacou, 2016). Withdrawal symptoms can occur following abrupt cessation of the drug after only 3 to 4 weeks of regular use (Brett & Murnion, 2015).…”
Section: Benzodiazepinesmentioning
confidence: 99%